Pengaruh Fasilitas dan Atraksi Wisata Pada Revisit Intention di Desa Wisata Saung Ciburial Garut yang dimediasi Dengan Kepuasan Wisatawan - Adiatma, Dani; Rukma, Deden Firman Syuyaman; Badriah, Shifa Siti (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of facilities and tourist attractions on revisit intention, mediated by tourist satisfaction, at Saung Ciburial Tourism Village, Garut. The type of research used is quantitative with a descriptive–verificative approach. The analytical method employed is path analysis based on Partial Least Squares–Structural Equation Modeling (PLS-SEM), as it is appropriate for testing the causal relationships among latent constructs with a relatively small sample size. The research population consists of all tourists visiting Saung Ciburial (population size unknown). The sample comprises 100 respondents obtained through a non-probability sampling technique, namely accidental sampling, involving visitors who met the inclusion criteria during the data collection period. A Likert-scale questionnaire instrument was used to measure tourists’ perceptions of facilities, attractions, satisfaction, and revisit intention. The research location is Saung Ciburial Tourism Village, Garut Regency, West Java. The analysis results show that facilities and attractions significantly affect satisfaction; satisfaction significantly influences revisit intention; and there are indirect effects of facilities and attractions on revisit intention through satisfaction. These findings underscore the importance of improving the quality of facilities and attraction management oriented toward satisfaction to encourage repeat visits. Keywords: facilities, tourist attractions, tourist satisfaction, revisit intention